La dimensión política de la historia en Hannah Arendt - Di Pego, Anabella (2004)
En este trabajo, nos proponemos analizar las similitudes en las concepciones de la historia de Hannah Arendt y Arthur Danto. Sobre la base de estas similitudes, y dada la anterioridad temporalde las obras de Arendt relevantes para este tema -mediados y fines de la década del 50- pretendemos mostrar que esta autora anticipó, en cierta medida, el enfoque general del narrativismohistórico iniciado con la publicación del libro de Danto ; Filosofía analítica de la historia ;en 1965.Por otra parte, sostenemos que a diferencia de Danto, Arendt no sólo se ocupa de los problemasepistemológicos de la historia sino también de las relaciones entre la historia y la política. Esta peculiaridad del enfoque de Arendt, que denominaremos dimensión política de la historia,desempeña un papel central en el fortalecimiento del espacio público
The aim of this paper is to analyze the similarities in terms of historical conceptions between Hannah Arendt und Arthur Danto. On the basis of those similarities, and in view of the fact that the works of Arendt related to this subject were published before those of Danto -middle and late 50s- we will try to show how this authoress anticipated, in a certain way, the general approach of historical narrativism that began with Danto's publication in 1965 of his book Analytical Philosophy of History. We also consider that, unlike Danto, Arendt deals not only with the epistemological issues of History but also with the relationship between History and Politics. This particular aspect in Arendt's approach, that we will call the political dimension of History, plays a key role in the strengthening of the public sphere
Keywords: Historia; Narración; Acción; Política; Espacio público; History; Story; Action; Politics; Public sphere; Historia; Política; Arendt, Hannah; Danto, Arthur; Filosofía contemporánea